Seroepidemiological analysis of anti-pneumococcal surface protein A (PspA) immunoglobulin G by clades in Japanese population. Issue 47 (3rd November 2020) - Morino, Saeko; Kitagami, Etsuko; Nakayama, Hiroki; Koizumi, Yuka; Tanaka-Taya, Keiko; Kinjo, Yuki; Oishi, Kazunori
Highlights: PspA is a candidate of the novel pneumococcal protein vaccines. We examined anti-PspA IgG concentrations by clades (1, 2, 3, 4, and 5) in 397 sera. Most people acquired anti-PspA IgG across clades 1, 2, 3, 4, and 5 during childhood. Positive correlations were shown between clades, especially within same family. Abstract: Background: Pneumococcal surface protein A (PspA) is one of the candidates of the novel pneumococcal protein vaccines. The seroepidemiology of naturally acquired anti-PspA immunoglobulin G (IgG) by clades, across a wide range of ages has not been investigated. Methods: We examined the concentrations of anti-PspA IgG by clades (1, 2, 3, 4, and 5) in 397 sera from persons aged 0–≥70 years by enzyme-linked immunosorbent assay, and determined the geometric mean concentrations (GMCs) by age group. The relationships between concentrations of anti-PspA IgG antibody for each clade for each person were also assessed. Results: GMC of anti-PspA IgG was lowest, highest, and plateaued in those aged 6–11 months, 5–9-years, and 20–49 years, respectively. It gradually declined in those aged > 70 years. GMCs patterns in different age groups were similar for all clades. Correlations were found especially within the same PspA family (between clades 1 and 2 or clades 4 and 5). Conclusions: Our data suggested that most people acquired anti-PspA IgG across clades 1, 2, 3, 4, and 5 during childhood. These results would be a fundamental data of clade-specific anti-PspA IgG antibodies.